Probing QGP-like Dynamics via Multi-Strange Hadron Production in High-Multiplicity pp Collisions - Haifa I. Alrebdi; Muhammad Ajaz; Muhammad Waqas; Maryam Waqar; Taoufik Saidani (Particles, 2025)
This study employs Monte Carlo (MC) models and thermal-statistical analysis to investigate the production mechanisms of strange (<semantics><msubsup>KS0</msubsup></semantics>, <semantics>Λ</semantics>) and multi-strange (<semantics>Ξ</semantics>, <semantics>Ω</semantics>) hadrons in high-multiplicity proton–proton collisions. Through systematic comparisons with experimental data, we evaluate the predictive power of EPOS, PYTHIA8, QGSJETII04, and Sibyll2.3d. EPOS, with its hydrodynamic evolution, successfully reproduces low-<semantics>pT</semantics><semantics><msubsup>KS0</msubsup></semantics> and <semantics>Λ</semantics> yields in high-multiplicity classes (MC1–MC3), mirroring quark-gluon plasma (QGP) thermalization effects. PYTHIA8’s rope hadronization partially mitigates mid-<semantics>pT</semantics> multi-strange baryon suppression but underestimates <semantics>Ξ</semantics> and <semantics>Ω</semantics> yields due to the absence of explicit medium dynamics. QGSJETII04, tailored for cosmic-ray showers, overpredicts soft <semantics><msubsup>KS0</msubsup></semantics> yields from excessive soft Pomeron contributions and lacks multi-strange hadron predictions due to enforced decays. Sibyll2.3d’s forward-phase bias limits its accuracy at midrapidity. No model fully captures <semantics>Ξ</semantics> and <semantics>Ω</semantics> production, though EPOS remains the closest. Complementary Tsallis distribution analysis reveals a distinct mass-dependent hierarchy in the extracted effective temperature (<semantics>Teff</semantics>) and non-extensivity parameter (q). As multiplicity decreases, <semantics>Teff</semantics> rises while q declines—a trend amplified for heavier particles. This suggests faster equilibration of heavier particles compared to lighter species. The interplay of these findings underscores the necessity of incorporating QGP-like medium effects and refined strangeness enhancement mechanisms in MC models to describe small-system collectivity.